Active-to-Sedentary Behavior Transitions, Fatigability, and Physical Functioning in Older Adults - Schrack, Jennifer A (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: With aging, daily physical activity (PA) becomes less frequent and more fragmented. Accumulation patterns of daily PA—including transitions from active-to-sedentary behaviors—may provide important insights into functional status in older, less active populations. METHODS: Participants of the Baltimore Longitudinal Study of Aging (n = 680, 50% male, aged 27–94 years) completed a clinical assessment and wore an Actiheart accelerometer. Transitions between active and sedentary states were modeled as a probability (Active-to-Sedentary Transition Probability [ASTP]) defined as the reciprocal of the average PA bout duration. Cross-sectional associations between ASTP and gait speed (m/s), fatigability (rating-of-perceived-exertion [RPE]), 400 m time (seconds), and expanded short physical performance battery score were modeled using linear and logistic regression, adjusted for chronic conditions. Further analyses explored the utility of ASTP over-and-above total daily PA. RESULTS: In continuous models, each 0.10-unit higher ASTP was associated slower gait (β = −0.06 m/s, SE = 0.01), higher fatigability (β = 0.60 RPE, SE = 0.12), slower 400 m time (β = 16.31 s, SE = 2.70), and lower functioning (β = −0.13 expanded short physical performance battery score, SE = 0.03; p < .001). In categorical analyses, those in the highest tertile of ASTP were >2 times more likely to have high fatigability (rating of perceived exertion ≥10), slow 400 m time (>300 seconds) and reduced functional performance (expanded short physical performance battery score < 3.07) than those in the lowest tertile (p < .01). Further analyses demonstrated ASTP provided additional insight into functional outcomes beyond total daily PA. CONCLUSION: Fragmented daily PA—as measured by ASTP—is strongly linked with measures of health and functional status and may identify those at risk of high fatigability and reduced functional performance over and above traditional PA metrics.